2010
DOI: 10.1111/j.1440-1746.2010.06385.x
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of liver stiffness measurement using FibroScan in chronic hepatitis C in South Korea: A multicenter, prospective study

Abstract: Aim: We investigated the accuracy of liver stiffness measurement (LSM) in chronic hepatitis C (CHC) in a multicenter, prospective study in South Korea. Methods: Between June 2005 and July 2009, 91 CHC patients without a previous history of antiviral treatment, clinical evidences of cirrhosis, coinfection with other viruses, and heavy alcohol consumption and with alanine aminotransferase (ALT) Յ 5x upper limit of normal, total bilirubin Յ 1.5 mg/dL, sufficient liver biopsy quality (Ն 15 mm and more than six por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 44 publications
2
24
1
Order By: Relevance
“…Therefore, as alternatives to liver biopsy, many noninvasive methods and scoring systems have been developed to assess the stages and dynamic changes of liver fibrosis. Currently, several advanced imaging technologies, including transient elastography, acoustic radiation force impulse elastography, and magnetic resonance imaging elastography, are utilised to measure hepatic fibrosis 911 . However, they are costly and not widely utilised by medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as alternatives to liver biopsy, many noninvasive methods and scoring systems have been developed to assess the stages and dynamic changes of liver fibrosis. Currently, several advanced imaging technologies, including transient elastography, acoustic radiation force impulse elastography, and magnetic resonance imaging elastography, are utilised to measure hepatic fibrosis 911 . However, they are costly and not widely utilised by medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, one multi-center cohort study reported the diagnostic performance of TE in populations with CHC (Table 1). 29 In this study, the optimal cutoff value for significant fibrosis was 6.2 kPa and that for cirrhosis was 11.0 kPa, which were more accurate than other non-invasive parameters such as aspartate aminotransferase (AST)-to-platelet ratio index (APRI) 29…”
Section: Diagnostic Performance Of Assessing Liver Fibrosismentioning
confidence: 71%
“…7,8,26 29. In these studies, the AUROC of TE ranged from 0.77 to 0.90, with a cutoff value of 6.2-8.7 kPa for assessment of significant fibrosis (F≥2), and an AUROC of 0.90-0.97 and cutoff value of 9.6-14.8 kPa for assessment of cirrhosis (Table 1).…”
Section: Diagnostic Performance Of Assessing Liver Fibrosismentioning
confidence: 94%
“…Weight, ALT level, and TB level were factors affecting the accuracy of the results . Numerous studies have described the detailed background and examination procedures of FS …”
Section: Methodsmentioning
confidence: 99%